CLINICAL AND IMMUNOLOGICAL CHARACTERISTICS OF DIABETES-ASSOCIATED OSTEOARTHRITIS - I. V. Shirinsky; N. Yu. Kalinovskaya; V. S. Shirinsky (Медицинская иммунология)
Osteoarthritis (OA) has been shown to be a heterogeneous disease. Diabetes mellitus (DM)associated represents a special OA subtype. Its clinical and immunological characteristics are poorly understood. To assess immune phenotype of the diabetes-associated OA and appropriate relationship between its clinical manifestations and cytokine concentrations in peripheral blood, we examined 78 patients with generalized OA including 52 patients in experimental group (82.6% females) who exhibited clinical manifestations of OA preceded by DM type II for, at least, 1 year, and 26 OA diabetes-free patients (84.6% females). We found that clinical manifestations of DM-associated OA were associated with increased body weight, more pronounced level of joint pains, longer duration of morning stiffness, decreased functionality of hands and large joints, impaired quality of life and more severe clinical pattern of the illness. Pronounced clinical manifestations in OA patients were more typical to the patients who required insulin therapy. The patients with DM type II-associated OA had elevated levels of proinflammatory (IL-6, IL-18) and reduced serum concentrations of anti-infammatory cytokines (IL-10, adiponectin), thus suggesting more pronounced systemic inflammation in patients of the first group. Concentrations of circulating IL-6 correlated with several functional indexes of OA severity. In conclusion, the DM-associated OA represents a special subtype of osteoarthritis, and deserves further studies of its immune pathogenesis and development of new treatment strategies.